ETHICAL ISSUES OF PLASTIC SURGERY - Xasanov Azim Mansurovich; Djumayev Akbar Anvarovich (KONFERENSIYALAR, 2025)
Аnnotation.  Each  epoch  set  its  own  priorities  regarding  the  value  of  the "inner"  (soul,  consciousness)  and  "outer"  (bodily)  in  a  person,  and  gave  the corporeality  itself  outlines  consistent  with  the  norms  of  beauty  transmitted  by culture and perceived by the subject.